2021
DOI: 10.9734/jpri/2021/v33i58b34186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Smoking Cessation on Lung Function Parameters – A Cross Sectional Study

Abstract: Background: There have been widespread adverse effects and association between smoking and tobacco use across published researches, but very few studies have been investigated on the beneficial effects that accompany a long-term cessation of smoking. Comparing the lung function with normal subjects might significantly use the results obtained, if positive, to encourage current smokers to quit smoking and quitters to continue to refrain from smoking.  Aims: To determine the impact of cessation of smoking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…A meta-analysis showed that that smoking negatively affect sperm parameters [32]. Conversly, other researchers have found that tobacco has no impact on standard semen parameters [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that that smoking negatively affect sperm parameters [32]. Conversly, other researchers have found that tobacco has no impact on standard semen parameters [33][34][35].…”
Section: Discussionmentioning
confidence: 99%